Hadith Criticism in the Al-Qur'an Textbook Hadith Madrasah Ibtidaiyah Class I - Fitri Wahyuni (al-Afkar, Journal For Islamic Studies, 2024)
The focus of this research is to examine and criticize the hadiths contained in the MI class I Al-Qur'an Hadith textbook. The aim of this research is to find out the hadiths contained in the MI class I Al-Qur'an Hadith textbook, both from editorial and translation aspects, explanation of the meaning and values ​​contained in the hadith, even in terms of the quality of the hadith as outlined in textbooks. The research method in this article uses a qualitative approach, with the type of library research or literature study (library research). The data collected will be processed and analyzed in depth using the takrijul hadith and ma'anil hadith methods. The results of this research show that: When referring to the principles of textbook development, this book is not yet proportional. Because the material outlined in the book is not balanced between aspects of the Koran and aspects of hadith; The hadiths contained in the book can be confirmed to be the hadiths narrated by Muslim imams. Because there is no difference between sanad and matan from Muslim shohih books and scriptures.